Interferences and Matrix Effects on Iron Isotopic Composition Measurements by 57Fe-58Fe Double-Spike Multi-Collector Inductively Coupled Plasma Mass Spectrometry; the Importance of Calcium and Aluminum Interferences - Lacan, F.; Artigue, L.; Klar, J. K.; Pradoux, C.; Chmeleff, J.; Freydier, R. (Frontiers in Environmental Chemistry, 2021)
Multi-Collector Inductively Coupled Plasma Mass Spectrometers (MC-ICPMS) are widely used for Fe isotope measurements. The latter may be perturbed by interferences (notably from Cr and Ni) and matrix effects (notably from major elements), caused by elements remaining in the samples after purification. We quantified some of these perturbations and our ability to correct them whenever possible, using Thermo Neptune and Neptune Plus MC-ICPMS with a 57-58Fe double spike mass bias correction. 54Cr and 58Ni isobaric interference corrections were found to be extremely efficient up to Cr/Fe=0.12 and Ni/Fe=0.04 (g/g natural Fe). Matrix effects were found negligible up to at least Na/Fe=175, Mg/Fe=10, K/Fe=1.5 and Mo/Fe=75 (g/g natural Fe). 28Si2+ interference was found negligible up to Si/Fe=50. Finally, we found that calcium and aluminum could cause significant interferences (e.g., 40Ca16O, 27Al2+), for Ca/Fe2.5 and Al/Fe2.5. The perturbation intensity relative to the Ca/Fe ratio was found dependent on the measurement conditions (plateau width). While working with samples with potentially high calcium or aluminum contents (such as calcite minerals or tests, bones and teeth, or marine samples and crustal rocks) we recommend to carefully take into account Ca and Al while tuning the instrument and checking the measurement accuracy with isotopic standards (i.e. doping the isotopic standard with Ca and Al levels comparable to those of the samples).